The Positive Effects of Priming Exercise on Oxygen Uptake Kinetics and High-Intensity Exercise Performance Are Not Magnified by a Fast-Start Pacing Strategy in Trained Cyclists - Correa Carita, Renato Aparecido [UNESP]; Greco, Camila Coelho [UNESP]; Denadai, Benedito Sergio [UNESP] (Public Library Science, 2014)
The purpose of this study was to determine both the independent and additive effects of prior heavy-intensity exercise and pacing strategies on the VO2 kinetics and performance during high-intensity exercise. Fourteen endurance cyclists (VO(2)max -62.8 +/- 8.5 mL.kg(-1).min(-1)) volunteered to participate in the present study with the following protocols: 1) incremental test to determine lactate threshold and VO(2)max; 2) four maximal constant-load tests to estimate critical power; 3) six bouts of exercise, using a fast-start (FS), even-start (ES) or slow-start (SS) pacing strategy, with and without a preceding heavy-intensity exercise session (i.e., 90% critical power). In all conditions, the subjects completed an all-out sprint during the final 60 s of the test as a measure of the performance. For the control condition, the mean response time was significantly shorter (p<0.001) for FS (27 +/- 4 s) than for ES (32 +/- 5 s) and SS (32 +/- 6 s). After the prior exercise, the mean response time was not significantly different among the paced conditions (FS=24 +/- 5 s; ES=25 +/- 5 s; SS=26 +/- 5 s). The end-sprint performance (i.e., mean power output) was only improved (similar to 3.2%, p<0.01) by prior exercise. Thus, in trained endurance cyclists, an FS pacing strategy does not magnify the positive effects of priming exercise on the overall VO2 kinetics and short-term high-intensity performance.